Selling Arms and Expressing Harm. Issue 1 (17th November 2020) - Christensen, James
Abstract: According to an argument commonly made by politicians, selling weapons to oppressive and aggressive regimes can sometimes be permissible because the sale renders the victims of these regimes no worse off than they would have been had the sale not been made. We can refer to this argument as the inconsequence argument . My primary aim in this article is to identify one reason why the inconsequence argument will often not succeed in vindicating arms sales to oppressive and aggressive regimes. The inconsequence argument will often not succeed because arms sales to oppressive and aggressive regimes often do make the victims of these regimes worse off than they would have been had the sales not gone ahead. The victims of these regimes are often made worse off in virtue of the fact that arms sales can generate expressed harms, which, unlike some of the material harms often engendered by such sales, are additive (rather than substitutive) in character. As I shall explain, expressed harms are similar to, but also significantly different from, expressive harms . The differences are important because they allow us to construct a reply that can answer the inconsequence argument on its own (consequentialist) terms.